2022
DOI: 10.21608/mjppf.2022.258984
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Irrigation Systems, Rates and Polymer on Water Use Efficiency, Yield and Fruit Quality of Grape Under Desert Conditions

Abstract: This experiment was carried out during the two successive seasons 2020 and 2021 on Flame Seedless grapevines grown in sandy soil under drip irrigation system at EL-Tahrir, El Beheira Governorate. The aim of this research was to save irrigation water without any reduction of water use efficiency, yield and fruit quality of Flame Seedless grapevines under desert condition. The experiment design was arranged in a split-plot with three replications. The main plots were divided into three drip irrigation systems, i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 10 publications
3
3
0
Order By: Relevance
“…This outcome is consistent with research on grapevines conducted by (Cabral et al, 2021 andCaruso et al, 2022). In addition, the increase in cluster weight and yield observed in irrigation treatments can be interpreted in view of the fact that these treatments led to the increase in the photosynthetic rate of leaves and then cluster enhanced (Rabeh et al, 2022). From the previous studies, it has been concluded that adding SAP can enhance the fruit's chemical and physical properties because of the prolonged soil moisture, enhanced microbial activity, and higher nutrient availability (Cerasola et al, 2022).…”
Section: Effect Of Superabsorbent Polymer (Sap) Under Different Irrig...supporting
confidence: 90%
See 3 more Smart Citations
“…This outcome is consistent with research on grapevines conducted by (Cabral et al, 2021 andCaruso et al, 2022). In addition, the increase in cluster weight and yield observed in irrigation treatments can be interpreted in view of the fact that these treatments led to the increase in the photosynthetic rate of leaves and then cluster enhanced (Rabeh et al, 2022). From the previous studies, it has been concluded that adding SAP can enhance the fruit's chemical and physical properties because of the prolonged soil moisture, enhanced microbial activity, and higher nutrient availability (Cerasola et al, 2022).…”
Section: Effect Of Superabsorbent Polymer (Sap) Under Different Irrig...supporting
confidence: 90%
“…Since SAP can effectively boost water efficiency and water use efficiency by increasing the quantity of water-stable aggregates and preventing water evaporation from the soil (Zhao et al, 2019), it shows a significant improvement in sandy soil and arid locations (Bai et al, 2010). Our results are in agreement with (Rabeh et al, 2022) who found that SAP significantly increased the water use efficiency of (Flame Seedless) grapevines grown in sandy soil under a drip irrigation system.…”
Section: Effect Of Superabsorbent Polymer (Sap) Under Different Irrig...supporting
confidence: 90%
See 2 more Smart Citations
“…These outcomes agree with those that were already reached by Genaidy et al (2016 ) who stated that IWUE was significantly increased with the decrease in irrigation amounts. In addition, Wei et al (2017) andRabeh, et al (2022) stated that grapevines irrigated at 75% of their water requirements improved the water use efficiency as compared with those irrigated at 100% or 50% of their water requirements. More improvement in WUE was noticed with the addition of 2kg/vine hundz soil under irrigation at 70% IWR, which reflects an increase in the ability of soil to retain water by adding natural soil conditioners such as hundz soil, The results is in good agreement whit those recorded whit (Ezzat et al, 2011) who stated that applying soil amendments, to sandy soil improves the soil's physical properties and decreases water loss by drainage leading to rationalization of irrigation water, and increasing irrigation water efficiency…”
Section: Discussionmentioning
confidence: 99%